Stability of Jet Flows and Their Combustion (Review) - V.V. Kozlov (Учёные записки Казанского университета: Серия Физико-математические науки, 2015)
A review of the recent studies on the instability of jet flows and the influence of flow instability on microjet combustion processes is presented. The results of a vast experimental campaign undertaken to investigate the structure and development characteristics of subsonic round and plane macro- and microjets are given. Some peculiarities in the development of these flows depending on the initial conditions at the nozzle exit and the acoustic influence are highlighted. An opportunity to control the structure of round and plane macrojets by changing the mean velocity profile between the “top-hat” and parabolic shapes is found. New phenomena associated with the influence of transverse acoustic field on the microjet and microjet combustion are found.